Price Clustering of Chinese IPOs: The Impact of Regulation, Cultural Factors, and Negotiation. Issue 36 (2nd August 2019) - Hu, Bill; Jiang, Christine; McInish, Thomas; Ning, Yixi
ABSTRACT: During June 2009–May 2012, the China Securities Regulatory Commission (CSRC) suspended window guidance that limits issue prices. Using this regime change as a natural experiment, we test the combined effects of regulation, culture, and negotiation on price clustering of Chinese IPOs. The proportion of IPOs priced on round number 0 increases from 42.58% during sample periods with window guidance to 79.81% during sample period without window guidance, a level similar to that reported in developed markets . Moreover, we document a connection between whole CNY pricing of Chinese IPOs and several uncertainty measures including a unique uncertainty proxy defined as the time gap between the IPO date and the listing date. Second to the round number 0, issuing firms favour number 8 that associates with fortune, particularly during sample periods with window guidance. Our findings that price restrictions limit the power of negotiations but not the influence of cultural factors contributing to the understanding of price formation process.